Preparing for Tomorrow: A Case Study of Workforce Planning in North Carolina Municipal Governments - Jacobson, Willow S. (Public personnel management, 2010)
Local governments are poised for a workforce crisis. Many will be faced with the impact of a mass exodus of baby boomers from their ranks at the same time the skills and knowledge required to continue to provide quality services increases. Governments will compete with private and non-profit organizations, as well as with each other, for talented workers. However, this crisis is likely to be felt by governments first because of their older employee base and high demand for knowledge workers. Individuals with needed skills and knowledge will become harder to recruit and retain, especially if governments are not clear about the skills they seek. Workforce planning can help governments act and perform strategically in the face of increasingly complex governmental demands made even more challenging by this impending human capital crisis. The 2002 International Personnel Management Association report, Workforce Planning Resource Guide for Public Sector Human Resource Professionals, found that “Workforce planning is the most critical human resource management challenge in the public sector today.” This paper examines the state of workforce planning in North Carolina municipalities. Survey data from medium and large size municipalities in North Carolina with populations over 15,000 is analyzed to determine the current state of their workforce planning efforts. An overview of current practices, identified needs, pressing concerns, and primary barriers to implementation and success are presented.